Local-Cultural Values In Architectural Student Designs : Local-Cultural Values In Architectural Student Designs - Putra, Riza Aulia; Binti Bakri, Maysarah (Jurnal Koridor, 2022)
Architectural education has an essential role in shaping the mindset of students that impacts the ability of conceptualization in the design process. As the core subject, Architectural Design Studio (ADS) influences the students, particularly in terms of design. Being the architect candidate, the student is encouraged to elaborate on local-cultural values in their design, so that, the student will design a building that reflects a specific region and become the image of the place. Incorporating cultural values into the ADS assignment is one effective way to encourage students elaborate and design the built environment with a cultural approach. This research aims to see students’ competence in elaborating local-cultural values in their design and to assess the quality of cultural values implementation in ADS 5 assignment of Architecture Department Universitas Islam Negeri Ar-Raniry Banda Aceh’s student. The research method is descriptive and qualitative. The participant in this study is a student enrolled in ADS 5 during the 2018/2019 semester. The student design projects as the main data are analyzed using a semiotic analysis approach. The result indicates that the characteristic of the stilt house and the characteristic triangle-shaped are the most frequently applied characteristic of the student design.